Optimized Adhesion of Plated Silicon Solar Cell Contacts by F2‐Based Dry Atmospheric Pressure Nano‐Roughening. Issue 21 (8th August 2018) - Büchler, Andreas; Kafle, Bishal; Weber, Julian; Meyer, Fabian; Brand, Andreas A.; Maier, Alexander; Hofmann, Marc; Kluska, Sven; Bartsch, Jonas; Glatthaar, Markus
Abstract : The adhesion of a plated layer on a substrate is increased by an appropriate roughness at the interface. The paper reports on plated Ni‐Cu‐Ag contacts for silicon solar cells deposited into passivation layer openings that are created using a nano‐second pulsed laser. The adhesion of plated contacts on ns‐pulsed laser‐structured silicon ab initio is not sufficient. This is attributed to an improper surface topography. Atmospheric pressure dry etching in F2 is introduced as plating pre‐treatment to generate a beneficial nano‐roughness on the silicon substrate. Until now, this method is used in silicon photovoltaics only for the formation of black silicon. Process parameters are adjusted to allow the formation of cavities in the range of 5–30 nm. Thereby, the contact adhesion increases. In peel force tests on busbars, the average peel‐force raised from 0.3 to 2 N mm −1 . In sheer‐test on finger contacts an increase of maximum sheer force and a decreasing length of the finger displacement are observed. Due to the high etch selectivity between silicon and silicon nitride, no additional etch mask is required to protect the passivation layer. As precursors with a non‐optimized emitter design are used, the roughening procedure affects the solar cell efficiency. Abstract : Atmospheric pressure dry etching in F2 is introduced as plating pre‐treatment to generate a beneficial nano‐roughness on the silicon substrate. The method is shown to improve the adhesion of solar cell contacts that are structured by local ablation of the passivation layer using ns‐pulsed lasers.